Changes in salivary protein composition of lambs supplemented with aerial parts and condensed tannins: extract from Cistus ladanifer L. - a preliminary study. - Lamy, Elsa (2020)
Cistus ladanifer L. is a shrub present in Mediterranean areas without major use, but which can be incorporated into ruminant diets, improving the digestive efficiency of dietary protein and product quality. The high levels of plant secondary metabolites, including condensed tannins, may be responsible for the beneficial properties of the plant, but can also reduce palatability. In this study, C. ladanifer was incorporated into lambs’ diets, either as aerial parts or as a condensed tannin extract, reaching 1.25% and 2.5% of condensed tannins of dry matter. Saliva was collected and electrophoretic profiles of both whole saliva and saliva after in vitro incubation with C. ladanifer tannins were compared. Animals receiving the aerial parts of C. ladanifer decreased feed ingestion. Differences in salivary protein profiles were observed for animals fed with the higher levels of aerial parts of the plant (CL2.5 group). Most of the lambs’ salivary proteins were present in the precipitate formed after tannin-saliva incubation, and one of the bands increased in CL2.5 group was present in high proportion in the precipitate. None of the protein bands stained pink with Coomassie Brilliant Blue, suggesting the absence, or low amounts, of proline-rich proteins in lamb saliva. The results suggest that the aerial parts of C. ladanifer are poor in palatability and that salivary proteins from lambs, due to their affinity for this plant’s secondary metabolites, can contribute to this. Further protein identification is needed, as well as studies to access the stability of the tannin-protein complexes through the gastrointestinal tract.